Support for Aboriginal and non-Aboriginal Australian students' wellbeing at school. (2020) - Dillon, Anthony; Craven, Rhonda G.; Kaur, Gurvinder; Yeung, Alexander Seeshing
Highlights: Aboriginal students scored lower than non-Aboriginal students for all sources of support. Aboriginal students scored lower than non-Aboriginal students for all measures of wellbeing. Family support is more likely to contribute to wellbeing for Aboriginal students. Abstract: Appropriate support is crucial for Australian Aboriginal students to do well. The purpose of this paper was to investigate relations between 3 sources of educational support and 5 wellbeing outcomes for Aboriginal and non-Aboriginal Australian students and how these relations may differ for each group. Data were collected from students in Years 4–6 ( N = 660) from 171 primary schools in the state of New South Wales, Australia. Findings not only further revealed that there is a need to improve the psychosocial wellbeing of Aboriginal students in Australia, but also suggest that to improve wellbeing, educational support needs to be provided from various sources, including working with Indigenous families to capitalize on family support for the wellbeing of Aboriginal students.